Riots on the News in West Borneo - Dian Kartika Sari (Al-Albab, 2014)
Book Review: Zaenuddin H. Prasojo, Riots on the News in West Borneo Pontianak: STAIN Pontianak Press, 2008 West Borneo had a long story of visible social conflict among ethnics dwelling within different parts of regencies in the West Borneo many years ago. The conflict itself was not merely about the distinction of ethnicity, however, the powerful factors contributed to the event namely social and economic. Furthermore, the conflict which turned to violence became a global issue since mass media kept an eye on the news intensely. The news, moreover, could shower peace among the audience, on the other hand could aggravate the riot. Thus, the issue of conflict studies or conflict resolution has caught the attention of many scholars to learn more about conflict from all over the world. One of the scholars who also concerns on the conflict and originally comes from West Borneo, Zaenuddin has written a book about conflict studies, “Riots on the News in West Borneo”. This book, actually, is the development of his thesis, hence, it would be highly recommended for those who concerns on anthropology, social, and cultural issues to consume this book.